Impact of genomic alterations on outcomes in myelofibrosis patients undergoing JAK1/2 inhibitor therapy - Spiegel, Jay Y. (Blood Adv, 2017)
In myelofibrosis (MF), driver mutations in JAK2, MPL, or CALR impact survival and progression to blast phase, with the greatest risk conferred by triple-negative status. Subclonal mutations, including mutations in high–molecular risk (HMR) genes, such as ASXL1, EZH2, IDH1/2, and SRSF2 have also been associated with inferior prognosis. However, data evaluating the impact of next-generation sequencing in MF patients treated with JAK1/2 inhibitors are lacking. Using a 54-gene myeloid panel, we performed targeted sequencing on 100 MF patients treated with ruxolitinib (n = 77) or momelotinib (n = 23) and correlated mutational profiles with treatment outcomes. Ninety-nine patients had at least 1 mutation identified, 46 (46%) had 2 mutations, and 34 (34%) patients had ≥3 mutations. Seventy-nine patients carried a mutation in JAK2V617F, 14 patients had mutations in CALR, 6 patients had an MPL mutation, and 2 patients were triple negative. No mutation was significantly associated with spleen or anemia response. A high Dynamic International Prognostic Scoring System score and pretreatment transfusion dependence were associated with a shorter time to treatment failure (TTF), and this association retained significance on multivariable analysis. Patients with ASXL1 (hazard ratio [HR], 1.86; P = .03) and EZH2 mutations (HR, 2.94; P = .009) and an HMR profile (HR, 2.06; P = .01) had shorter TTF. On multivariate analysis, ASXL1 or EZH2 mutations were independently associated with shorter TTF and overall survival. These findings help identify patients unlikely to have a durable response with current JAK1/2 inhibitors and provide a framework for future studies.